Progesterone concentrations, estrous response, and fertility in beef heifers after estrous synchronization using melengestrol acetate® and prostaglandin F2α - C.W. Peters; Robert L. Larson; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1993)
Melengestrol acetate (MGA®) and prostaglandin F2α(PG; Lutalyse®) were used to synchronize estrus in 757 yearling, virgin, beef heifers on six commercial ranches. Heifers were inseminated artificially (AI) 12 h after first detected estrus; those not detected in estrus were time-inseminated 72 h post-PG injection. Heifers detected in estrus by 72 h had higher AI and overall pregnancy rates than their counterparts not detected in estrus. Heifers with serum progesterone>1 ng/ml at PG administration were generally more fertile than those with progesterone/ml. Of the heifers not detected in estrus and with low progesterone (/ml), 24% still conceived to the timed insemination at 72 h, but only 73% became pregnant during the entire breeding period. Overall AI conception rate, based on estrous detection and timed insemination, was 49% and varied from 24% to 69% among the six ranches. Heifers exhibiting estrus and with elevated (>1 ng/ml) serum progesterone showed acceptable pregnancy rates (63% AI and 94% overall).
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Melengestrol acetate; Prostaglandin; Beef heifers; Fertility; Estrus; Progesterone